1995
DOI: 10.1159/000184239
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Autoimmunity and Ageing

Abstract: Ageing is associated with the appearance of several serum autoantibodies, including thyroid autoantibodies. The biological and clinical significance of this phenomenon is still unknown, since, with the exception of primary myxedema, the prevalence of clinically overt thyroid autoimmune diseases is not increased in the elderly. The peculiar link between autoimmune thyroid failure and ageing is also underscored by the high prevalence of subclinical hypothyroidism in elderly subjects with positive serum thyroid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…The estimates of TPO antibodies are much higher in older adults with SCH, ranging from 40% to 67% [13,18,21- 23], suggesting that the increased prevalence of thyroid antibodies in the elderly may reflect age-associated disease rather than normal age-related changes to the HPT axis. This is further supported by the findings by Pinchera et al [24], who found a similar incidence of circulating thyroid antibodies among healthy centenarians and younger healthy elderly individuals (aged 65 to 80) compared with young and middle-aged adults.…”
Section: Prevalencesupporting
confidence: 83%
“…The estimates of TPO antibodies are much higher in older adults with SCH, ranging from 40% to 67% [13,18,21- 23], suggesting that the increased prevalence of thyroid antibodies in the elderly may reflect age-associated disease rather than normal age-related changes to the HPT axis. This is further supported by the findings by Pinchera et al [24], who found a similar incidence of circulating thyroid antibodies among healthy centenarians and younger healthy elderly individuals (aged 65 to 80) compared with young and middle-aged adults.…”
Section: Prevalencesupporting
confidence: 83%
“…On the one hand, some research findings reveal a slight, stimulating influence of curcumin that does not lead to hyperthyroidism in 3-month-old male rats [19]. The stimulating activity of curcumin may counteract the hypothyroidism connected with ageing of the thyroid gland, whereas its antiinflammatory activity shown in a number of in vitro and in vivo studies is assumed to prevent autoaggressive diseases which more often affect the thyroid gland in elderly than in young [20][21][22][23]. On the other hand, some experiments conducted on mice have demonstrated hyperplasia of the thyroid gland after prolonged curcumin administration [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that the age-associated decline in ThAbs is specifically found in studies including only disease-free females aged above 65 years. In studies performed in unselected populations (including hospitalized patients), the rise in thyroid antibody frequency with age may persist in the older age groups (2).…”
Section: Discussionmentioning
confidence: 99%
“…Immunosenescence is a well-characterized phenomenon accompanying ageing and represents a malfunction of the immune system leading to both increased infection susceptibility and increased frequency of certain kinds of autoimmune disorders in older age (1,2). Several mechanisms have been postulated (3,4) including neuroendocrine changes (5).…”
Section: Introductionmentioning
confidence: 99%